PENCIPTAAN TIRAI IKAT CELUP DENGAN RAGAM HIAS ALAM MELAYU - Rahma, Sheyla; Tridjata, Caecilia; Murwanti, Aprina (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
The craft sector has great potential in Indonesia. According to data from the Ministry of Tourism and Creative Economy (Kemenparekraf), the craft sector contributed IDR 166.13 trillion to the national GDP in 2020. Based on the craft potential data, artists are interested in introducing diverse and unique Malay decorative motifs through tie-dye curtains to the wider community. This Creation Research uses a descriptive qualitative research type and a practice-based research method with a formalistic approach to analyze the aesthetic value of the visual elements of Malay tie-dye curtain works. This tie-dye curtain work is made on linen fabric using the tritik tie-dye technique. The dye used in the process of making the work is synthetic indigosol dye with a brush-dyeing technique. During the process of making this final project curtain, the Malay natural decorative motif was successfully applied well to the tie-dye curtain and was able to present the Malay natural atmosphere well.